On body memory and embodied therapy - Koch, Sabine C.; Caldwell, Christine; Fuchs, Thomas (Body, movement and dance in psychotherapy, 2013)
Whether in clinical or scientific contexts the phenomenon of body memory has become a central topic of interest within embodied and embedded theory approaches. Between 2000 and 2012, Prof. Dr. Thomas Fuchs - professor for philosophical foundations of psychiatry at the University of Heidelberg - has put forth a theory on the phenomenology of body memory (Fuchs, 2012). The professional mission of Prof. Fuchs is to combine a philosophical approach based on phenomenology with psychiatric experience. More specifically, his aim is to describe the structures of subjective experience as an embodied way of being in the world and with others, and to investigate the disturbances that arise in this way of being. Based on an interview with Prof. Fuchs and Prof. Caldwell, who uses body memory in her clinical work, this article introduces the concept of body memory and connects it with applications in embodied psychotherapy.